2019
DOI: 10.1111/1467-9817.12276
|View full text |Cite
|
Sign up to set email alerts
|

Specific relevance instructions promote selective reading strategies: evidences from eye tracking and oral summaries

Abstract: Background The present study analysed how relevance instructions affect eye movement patterns and the performance in a summary task of six expository texts. Methods Forty‐one undergraduate students participated in the experiment; half of them were instructed to make an oral summary of the main ideas focusing on the ‘why’ question that appeared at the end of the first paragraph (specific relevance instruction), while the other half were instructed to make an oral summary of the main ideas of the text (general r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 47 publications
3
14
0
9
Order By: Relevance
“…The present results are in line with previous studies showing that task-relevance increases processing effort and subsequent recall of text information [ 21 , 25 , 26 , 8 , 9 , 16 ], and expand these earlier findings by showing that there are individual differences in how readers make use of this selective attention strategy. Unfortunately, on the basis of the current data, it is impossible to say what the underlying factor for these differences is.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present results are in line with previous studies showing that task-relevance increases processing effort and subsequent recall of text information [ 21 , 25 , 26 , 8 , 9 , 16 ], and expand these earlier findings by showing that there are individual differences in how readers make use of this selective attention strategy. Unfortunately, on the basis of the current data, it is impossible to say what the underlying factor for these differences is.…”
Section: Discussionsupporting
confidence: 93%
“…The present study examined how readers who produce good quality summaries process text information during the course of reading. The results showed that readers who demonstrate good summarization skills show strategic reading behavior (Hyönä et al, 2002) and utilize a selective processing strategy (Kaakinen et al, 2002(Kaakinen et al, , 2003León, Moreno, Escudero, Olmos, Ruiz & Lorch, 2019): they spend more time reading question-relevant than question-irrelevant paragraphs, and this preference is seen already during the first-pass reading of the relevant paragraphs. Readers who produce high quality summaries also do longer look-backs to the relevant paragraphs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Como consecuencia de ello, solo aquella información del texto que es relevante para cumplir con el objetivo lo será también para el lector (McCrudden, 2011;McCrudden y Schraw, 2007). Este tipo de lector, por lo tanto, focalizará su atención en el procesamiento de aquellos segmentos textuales que contienen información relevante para la tarea a desarrollar (Cerdán et al, 2013;León et al, 2019). En este estudio se emplearon instrucciones de relevancia, con el objetivo de gatillar un procesamiento focalizado y eficiente del texto, permitiendo que el lector definiera objetivos a partir de las instrucciones (McCrudden y Schraw, 2007).…”
Section: Establecimiento De Objetivos Y Comprensión Lectoraunclassified